Regulating procurement : understanding the ends and means of public procurement regulation - Trepte, Peter (O.U.P. OxfordGB, 2004)
Focuses on the public procurement function as exercised by the government agents responsible for the procurement decision. Deals with the government buyer and investigates the problems caused by the identity of that buyer and the tensions which arise when the otherwise purely economic purchasing function is coloured by the buyer's additional political and social resporsibitioies and international obligations.